Historique des crues et risque d’inondation dans la vallée de la Meurthe depuis le XVIIIe siècle - Claire Delus; Éric Bonnot; Didier François; Thomas Lejeune; Xavier Rochel; Denis Mathis; Jean Abèle (VertigO)
Historical studies are a fundamental aspect of natural risk prevention policies. This work presents the results of the flood history of the river Meurthe carried out as part of the development of an Action and Flood Prevention Programme (PAPI). Based on hydrometric archives water level series observed since the beginning of the 19th century were reconstructed. Documentary evidences are used to enlarge the record period to the last three centuries. This work may constitute a basis for analyzing the evolution of hazard and flood risk in the studied area, but also underline the difficulty of determining the factors of the variability in hydrological extremes. As historical flood study is now a prerequisite in the PAPI files, this type of study is likely to become widespread on many rivers.historical floods, hydrometric archives, geohistory, Meurthe basin